KISAH DAN DAKWAH MENURUT ALQURAN (SUATU PENDEKATAN KEBAHASAAN) - Hasan, M. (Institut Agama Islam Negeri (IAIN) Palu, 2005)
In the Holy Qurâan there are several narratives that tell past events along with their actors and their places such as the narrative of prophets, past events that can occur again in the future such as the narrative on the killing of Habil by Qabil, or symbolic narrative describing no event but can occur in the future. The main objective of the expression of narrative in the Holy Qurâan is to spread Islamic mission. This can be seen from Quraânic instruction to people to observe the creation of the universe, past events and questions asked, all of which order them to think of themselves andÂ their surroundings.Â Kata kunci : Alquran, kisah, dakwah